Konflik tambang emas Sulawesi Utara: Pertambangan emas tanpa izin (PETI) - Mustafa, Annisa Fitri (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Indonesia, a nation endowed with vast natural resources, confronts the task of ensuring sustainable resource management as stipulated in its 1945 Constitution, which emphasizes state authority for the well-being of its citizens. The proper usage of natural resources is vital for economic progress. The mining sector, including gold mining, has a notable impact on regional development by fostering economic growth and enhancing livelihoods.Sulawesi Utara, a province abundant in mineral and coal resources, is home to five gold mining firms operating under government contracts, as well as an additional 13 enterprises having Mining Business Licenses (IUP). Although there are regulatory frameworks in place, the region is vulnerable to Unlicensed Gold Mining Activities (PETI) due to the community's access to resources. Insufficient knowledge and technology cause communities to autonomously handle local mineral resources, resulting in the existence of approximately 2,700 PETI sites across the country. This article focuses on two primary concerns: the widespread occurrence of Unlicensed Gold Mining (PETI) in contravention of established regulations and the potential ecological consequences resulting from these operations. The paper examines the legal framework, namely Ministerial Regulation No. 19 of 2020, which governs mining activities in Indonesia. Some gold mining enterprises may not comply with rules, which creates environmental hazards as a result of illicit actions. The aim of this paper is to examine and assess the frequency of PETI practices in Sulawesi Utara, with a particular focus on their lack of adherence to current laws and regulations. The report seeks to offer guidance to local governments on effectively tackling PETI-related concerns, guaranteeing sustainable management of resources, and minimizing potential environmental consequences.